2012
DOI: 10.1186/2251-6832-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Techno-economic analysis of a hybrid mini-grid system for Fiji islands

Abstract: This study evaluates whether a transition of large ports facilities to biofuel production for mobility improves the environmental performance and satisfies the renewable energy directive (RED) and it is the first LCA study that considers biofuel production from torrefied wood. The systems studied are wood, torrefied wood, and straw pellets circulating fluidized bed gasification for H 2 , synthetic natural gas, or Fischer-Tropsch (FT) diesel production and use. These systems are evaluated for their global warmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…Fahmy et al [24] has shown that PV-wind hybrid system is better alternative in comparison to stand-alone wind and PV system for powering brackish water reverse osmosis desalination system for the region in Hurghada in Egypt. Lal and Raturi [25] investigates the feasibility of a wind-PV-diesel generator based hybrid power system for a remote location on the island of Vanua Levu, Fiji. Essalaimeh et al shows an experimental investigation of using a combination of solar and wind energies as hybrid system for electrical generation under the Jordanian climate conditions [26].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Fahmy et al [24] has shown that PV-wind hybrid system is better alternative in comparison to stand-alone wind and PV system for powering brackish water reverse osmosis desalination system for the region in Hurghada in Egypt. Lal and Raturi [25] investigates the feasibility of a wind-PV-diesel generator based hybrid power system for a remote location on the island of Vanua Levu, Fiji. Essalaimeh et al shows an experimental investigation of using a combination of solar and wind energies as hybrid system for electrical generation under the Jordanian climate conditions [26].…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Since wind is an intermittent source of energy, it is integrated with a diesel generator which serves as an alternate source of energy. Micro-grids are systems with clusters of loads and microsources [5][6][7][8]. If the micro-grid is wind based, the high penetration of wind energy along with different types of loads is a cause for power quality issues.…”
Section: Introductionmentioning
confidence: 99%
“…The former investigated the performance of the hybrid system under Martin Island climatic conditions whereas the latter has considered a small village in Comilla. Lal and Raturi [21] have carried out an economic assessment of PV-Wind-Diesel hybrid power system for a remote location on the island of Vanua Levu.…”
Section: Introductionmentioning
confidence: 99%